Pengaruh Jenis Kelamin dan Kreativitas terhadap Efektivitas Mengajar pada Masa Pandemi Covid-19 (Ex Post Facto pada Guru di Indonesia) - Iswadi Idris; Elin Karlina (Neolectura, 2021)
This study aims to determine 1). The effect of gender on the effectiveness of teaching teachers during the pandemic in Indonesia, 2) The effect of creativity on the effectiveness of teaching teachers during the pandemic in Indonesia, 3) The effect of the interaction between gender and creativity on the effectiveness of teaching teachers during the pandemic in Indonesia. The research method is quantitative with an ex post facto approach. The population is teachers in Indonesia, totaling 112. The number of samples is 88 teachers calculated by the Slovin Formula with a precision value of 95% or sig. = 0.05. The sampling technique is random or random sampling. Data collection techniques with questionnaires. Data analysis techniques with the help of SPSS Version 22. The results of the study are as follows: 1). There is no significant effect of gender on the effectiveness of teaching teachers during the pandemic in Indonesia, 2) There is a significant effect of creativity on the effectiveness of teaching teachers during the pandemic in Indonesia, 3) There is no interaction effect between gender and creativity on the effectiveness of teaching teachers in Indonesia. the pandemic period in Indonesia. The implications of this study are as follows. The effectiveness of teaching teachers during the pandemic does not depend on the gender of the teacher, but depends on the creativity of the teacher in teaching, namely the creativity of the teacher in using learning media to make it easier for students to learn through online, providing motivation to learn in an effective way by using videos containing learning motivations for students, using creative assessment techniques to measure student learning outcomes, and using creative learning methods so that the learning process during the pandemic can run effectively.